Emergence of Fluoroquinolone Resistance among Multiply Resistant Strains of Streptococcus pneumoniae in Hong Kong - Ho, Pak-Leung (American Society for Microbiology, 1999)
The MICs of 17 antimicrobial agents for 181 Streptococcus pneumoniae strains were determined by the E-test. Overall, 69.1% were penicillin resistant (MIC > 0.06 μg/ml). Resistance to ciprofloxacin (MIC > 2 μg/ml), levofloxacin (MIC > 2 μg/ml), or trovafloxacin (MIC > 1 μg/ml) was found in 12.1, 5.5, or 2.2% of the strains, respectively. These high rates of resistance raise concerns for the future.